To add insult to injury: Stigmatization reinforces the trauma of rape survivors - Findings from the DR Congo - Sabine Schmitt; Katy Robjant; Thomas Elbert; Anke Koebach (Elsevier, 2021)
Background: Survivors of sexual violence are frequently condemned and socially excluded. Myths about rape may translate into stigmatization, diminish disclosure, prevent help-seeking from support structures and worsen mental health. Areas of conflict or organized violence remain the evident hotspots of sexual victimization. However, little is known about prevalence and predictors of rape myths in these settings or their association with survivors' disclosure, stigmatization and psychopathology. Method: Between September 2018 and May 2019, we assessed in a representative sample of 1066 individuals from six communities in Eastern DRC traumatic exposure, sexual perpetration, threats to social integrity, perceived stigmatization (perceived lack of social acknowledgement, shame), stigmatizing attitudes towards survivors (negative attitudes and willingness to provide support, rape myths acceptance), and mental illness (PTSD, depression). Results: Survivors of sexual violence (33%, n = 184 of women, 16%, n = 84 of men) reported more traumatic exposure, threats to social integrity, shame, perceived lack of social acknowledgement, PTSD symptoms and depression. Their social environment affirmed various stigmatizing attitudes (5-89% affirmations). Beliefs in rape myths were predicted by its average acceptance in the community, education, and witness of others' sexual victimization. The rates of cases whose history of sexual victimization was socially disclosed were higher in communities and among survivors with low rape myths acceptance and disclosure showed associations with perceived stigmatization. Rape myths acceptance among individuals without a history of sexual victimization was associated with survivors' recently experienced threats to social integrity which predicted their stigma perceptions and mental illness. Conclusion: Rape myths acceptance in the community is associated with stigma and trauma-related mental illness of sexual violence survivors. This adds up to the psychic burden of trauma.